Magnetic and Mössbauer Spectroscopy Studies of Zinc-Substituted Cobalt Ferrites Prepared by the Sol-Gel Method - Qing Lin (Materials, 2018)
Zinc ion-substituted cobalt ferrite powders Co1−xZnxFe2O4 (x = 0–0.7) were prepared by the sol-gel auto-combustion process. The structural properties and magnetic of the samples were investigated with X-ray diffraction (XRD), superconducting quantum interference device, and a Mössbauer spectrometer. The results of XRD showed that the powder of a single cubic phase of ferrites calcined when kept at 800 °C for 3 h. The lattice constant increases with increase in Zn concentration, but average crystallite size does not decrease constantly by increasing the zinc content, which is related to pH value. It was confirmed that the transition from ferrimagnetic to superparamagnetic behaviour depends on increasing zinc concentration by Mössbauer spectra at room temperature. Magnetization at room temperature increases for x ≤ 0.3, but decreases for increasing Zn2+ ions. The magnetization of Co0.7Zn0.3Fe2O4 reached maximum value (83.51 emu/g). The coercivity decreased with Zn2+ ions, which were doped on account of the decrease of the anisotropy constant.